2019
DOI: 10.1016/j.psychres.2018.12.121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sex differences in delusion-associated cognitive biases

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Patients with schizophrenia exhibit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
6
2
Order By: Relevance
“…In contrast, some earlier studies suggested that women exhibit greater cognitive impairment [27]. Lastly, some studies showed no statistically signifi cant diff erence in cognition between patients of different gender, which correlates with the results of this study [28][29][30]. Th is inconsistency of the results is probably due to diff erent strategies in sampling patients, their inadequate pairing or inadequate sample size.…”
Section: Number Of Patientscontrasting
confidence: 46%
“…In contrast, some earlier studies suggested that women exhibit greater cognitive impairment [27]. Lastly, some studies showed no statistically signifi cant diff erence in cognition between patients of different gender, which correlates with the results of this study [28][29][30]. Th is inconsistency of the results is probably due to diff erent strategies in sampling patients, their inadequate pairing or inadequate sample size.…”
Section: Number Of Patientscontrasting
confidence: 46%
“…We would like to highlight that our validation study sample had a similar proportion of men and women. To date, few studies have analyzed the presence of sex differences concerning cognitive biases in psychosis, finding no significant differences (66,67). However, de Vos et al (66) suggest the possibility of a subtle effect of sex differences related to delusion-associated cognitive biases, which is necessary to carry out more extensive studies with more statistical power to detect it (65).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have analyzed the presence of sex differences concerning cognitive biases in psychosis, finding no significant differences (66,67). However, de Vos et al (66) suggest the possibility of a subtle effect of sex differences related to delusion-associated cognitive biases, which is necessary to carry out more extensive studies with more statistical power to detect it (65). Indeed sex differences in cognitive biases could be expected because of these biases' link to neuropsychological performance (19,68,69) and global functioning (70) and the previously found differences between men and women concerning these domains (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring sex differences in social cognition and metacognition is inconclusive, probably due to the tendency to present averaged results [37]. A majority of studies have failed to find significant differences between sexes in social cognition [38][39][40] or metacognition [41,42]. However, exploring differences in social cognition and metacognition beyond mean differences has often led to the discovery of important results.…”
Section: Introductionmentioning
confidence: 99%